Characterization of antibodies to the insulin receptor: a cause of insulin-resistant diabetes in man. - Flier, J S (1976)
We have characterized the circulating inhibitor of insulin receptor binding found in several patients with a new syndrome of extreme insulin resistance. The inhibitor is an immunoglobulin by multiple criteria, including precipitation by 33% ammonium sulfate, migration on G-200 Sephadex gel filtration and DEAE chromatography, and immuno-precipitation with specific anti-human immuno-globulins. Although predominantly IgG, some activity is found in the IgM fraction of the immunoglobulins in one patient. The inhibitory immunoglobulins reacted with antisera to both kappa and lambda light chain determinants and are therefore polyclonal. In addition, activity is retained in the F(ab')2 fraction of pepsin-digested IgG. Evidence suggests that these antibodies are directed at determinants on or near the insulin receptor, and that they are responsible for the observed clinical insulin resistance.